Pengaruh Komunikasi Orang Tua dan Mahasiswa Perantauan terhadap Kemampuan Adaptasi Budaya di Kota Makassar (International Forum of Researchers and Lecturers, 2025)
The influence of communication is the most important thing in human life to provide support and good motivation to each other. The purpose of this study is to determine the Influence of Communication Between Parents and Migrant Students on Cultural Adaptation Skills in Makassar City, where the inhibiting factors are. In this study, the method used is a qualitative method, using data collection techniques, observation, interviews, and documentation. Based on the results of research in the field, it was obtained that the influence of communication between parents and migrant students on cultural adaptation skills in Makassar City was not optimal because it was seen from the low quality network so that communication between parents and migrant students was not in accordance with expectations. In addition, there is also a factor of lack of understanding of parents in operating the media accompanied by their respective busyness.